Profile of Reading Comprehension Skills In Narrative Texts Among Fifth Grade Elementary School Students - Siti Amalia, N. Yuniar Rizki; Heryani, Rina (International Conference on Elementary Education, 2025)
This study aims to describe the profile of fifth-grade elementary students’ reading comprehension in narrative texts based on four dimensions of Barrett’s taxonomy: literal, reorganization, inferential, and evaluative–appreciative comprehension. A quantitative descriptive approach was employed and supported by qualitative data. The research subjects consisted of 28 elementary school students. Quantitative data were collected through reading comprehension tests, while qualitative data were obtained from classroom observations, teacher interviews, and analysis of Indonesian language teaching modules. The data analysis technique used was Miles and Huberman with data analysis components, namely data reduction, data presentation, and conclusion drawing.The results of the study show that, in general, students' reading comprehension skills are still moderate to low. Of all participants, no students achieved the excellent category, while 21.4% were in the good category, 21.4% in the fair category, and the rest (57.2%) were still in the poor to very poor category. The highest achievement was seen in the literal aspect, which indicates that students are relatively able to recognize the information expressed in the text. However, in the reorganization, inferential, and evaluative appreciative aspects, most students showed difficulty in rearranging the plot, drawing implied meanings, and critically and reflectively assessing the content of the reading. These results indicate the need to apply more interactive and contextual learning strategies and media to improve the ability to understand the content of reading comprehensively